Indonesia : CPSS Core Principles for Systemically Important Payment Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents key findings of the Financial Sector Assessment Program for Indonesia. The program covers Bank Indonesia's real-time gross settlement (BI-RTGS) system's observance of the Committee on Payment and Settlement Systems (CPSS) core principles for systemically important payment systems (SIPS). The assessment reveals that the legal foundation for payment systems in Indonesia is generally sound with explicit provisions for the central bank's involvement in payment systems. The BI-RTGS generally functions well and is recognized as the only SIPS in Indonesia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet